The Effectiveness of Legal Protection for Abandonment of Wives by Husbands as a Form of Domestic Violence - Prasetyo Budi Utoyo; Indra Koswara; Yopie Gunawan (LEGAL BRIEF, 2022)
Integrity and harmony in the household will depend on everyone in the household, namely husband and wife, children and people in the family. Disorganized home harmony will mainly emerge and can be seen from the level of quality of behavior and control of everyone in the household. According to Article 1 Paragraph (1) of the Law on the Elimination of Domestic Violence, it is any act against a person, especially a woman, which results in